Development and Psychometric Validation of the Music Receptivity Scale - George, Mahesh; Ilavarasu, Judu (Frontiers in Psychology, 2021)
A new construct termed Music Receptivity is introduced and discussed in this work. Music Receptivity can be defined as a measure of the extent of internalization that an individual has, to a given piece of music, as measured at the point of listening. Through three studies we demonstrate the psychometric properties of this novel construct, Music Receptivity Scale (MRS). Exploratory factor analysis on a sample of 313 revealed good psychometric validity, with a four-factor solution (Emotional Experience, Interest, Attention and Hurdles), with a Cronbach’s alpha of 0.89, and a two-factor solution (Emotion Experience and Attention), with a Cronbach’s alpha of 0.87. The tool also had a good test-retest reliability (r = 0.87 for 15 days and r = 0.91 for one-month intervals). Overall, the tool had 20-items in the long form and 12 items in the short version. MRS could distinguish musicians and non-musicians supporting its discriminant validity. We have also discussed the implication of MRS in the field of music psychology.